Solid electrolyte and preparation method thereof, and secondary battery and device containing solid electrolyte
By combining polymer, lithium salt and inorganic ceramic filler, a new solid electrolyte was prepared, which solved the problems of unstable performance, poor circulation performance and high cost of solid electrolytes in the prior art, and achieved efficient and safe lithium metal Battery electrolyte.
Patent Information
- Application Number
- CN202311020771.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
The existing solid electrolytes have shortcomings in performance stability, cycle performance and cost, which limits their wide application in lithium metal batteries.
By combining polymer, lithium salt and inorganic ceramic filler, a new solid electrolyte is prepared. The inorganic ceramic filler consists of the first filler and the second filler. By adjusting the type and content of the filler, the ionic conductivity of the electrolyte is optimized. Interface contact performance and mechanical strength.
It achieves the improvement of high ionic conductivity, good interface contact performance and mechanical strength of solid electrolytes, while reducing the preparation cost, suitable for large-scale production, and improving the circulation performance and safety of lithium metal batteries.
Smart Images

Figure BDA0004395435390000141 
Figure BDA0004395435390000151
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a solid electrolyte and a preparation method thereof, and a secondary battery and a device comprising the solid electrolyte. Background Art
[0002] Rechargeable lithium-ion batteries are the most promising power source to meet people's demand for high energy density. However, the lithium-ion batteries currently on the market all contain organic liquid electrolytes, which may cause risks such as leakage and explosion during long-term cycles. Replacing liquid electrolytes and carbon-based negative electrode materials with solid electrolytes and lithium metal to form solid-state lithium metal batteries not only improves the safety of the battery, but also further reduces the volume and increases the energy density, giving it a broader application prospect. Solid electrolytes generally include inorganic solid electrolytes, polymer solid electrolytes, and composite solid polymer electrolytes. Polymer solid electrolytes include PEO, PVDF, PPC, PVP, etc., which have good contact properties with the positive and negative electrodes, but their limited ionic conductivity (<10 -6 S cm -1 ) limits its application. Inorganic solid electrolytes include LATP, LAGP, LLZO, LLZTO, LLTO, LZSP, LPS, LiPON, etc. They have high ionic conductivity (>10 -3 S cm -1 ), but their poor compatibility between positive and negative electrodes limits their application. In addition, LLZO and LLZTO have poor chemical stability, LATP and LAGP have poor electrochemical stability, and LZSP has high manufacturing cost and difficulty, which again limits their industrial application.
[0003] Therefore, we urgently need to find an economical solid electrolyte with excellent electrochemical performance. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present application provides a solid electrolyte and a preparation method thereof, a secondary battery and a device comprising the solid electrolyte. The solid electrolyte prepared by the present invention can overcome the problems of unstable performance of traditional solid electrolytes, poor cycle performance of batteries and high cost that are not conducive to large-scale production, and thus can be applied to solid-state secondary batteries.
[0005] The first aspect of the present application provides a solid electrolyte, including a polymer, a lithium salt and an inorganic ceramic filler; the inorganic ceramic filler includes a first filler and a second filler; based on the total mass of the solid electrolyte, the mass content of the first filler is A%, and the mass content of the second filler is B%; wherein 5≤A≤50; 0≤B≤25; 5≤A+B≤50; 0%≤B / A≤100%.
[0006] In some embodiments, 5≤A≤40; 0≤B≤20; 5≤A+B≤45; 0%≤B / A≤80%. The first filler comprises Li 3+X1 W X1 Zr 2-X1 Si2PO 12 , wherein 0≤X1≤2, W is at least one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y and Sn; the second filler includes Li 1+X2 M X2 (N 1Y1 ,N 2Y2 ,N 3Y3 ) 2-X2 (PO4)3、Li 7-X3 LqCy 2-X3 Ta X3 O 12 and Li 7+X4 Zn X4 La 3-X4 Zr2O 12 At least one of the following, wherein 0.1≤X2≤0.9, Y1+Y2+Y3=1, 0≤Y1 / Y2 / Y3≤1, M is at least one of Al, Ga, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb, N1, N2, N3 are at least one of Ti, Ge and Hf respectively, 0≤X3≤3, 0≤X4≤3.
[0007] The second aspect of the present application provides a method for preparing a solid electrolyte, which comprises: step 1, adding a polymer, a lithium salt, a first filler and a second filler in a mass ratio of (20-60): (10-50): (5-50): (0-25) to a solvent to prepare a mixed solution; step 2, removing the solvent from the mixed solution obtained in step 1 to obtain a solid electrolyte.
[0008] A third aspect of the present application provides a secondary battery, comprising the aforementioned solid electrolyte or a solid electrolyte prepared by the aforementioned method for preparing the solid electrolyte.
[0009] A fourth aspect of the present application provides a device comprising the aforementioned secondary battery.
[0010] Beneficial effects:
[0011] The present invention forms a solid electrolyte having high ionic conductivity and good interface contact performance by mixing inorganic ceramic fillers and polymers. Furthermore, by controlling the type and content of the first filler and the second filler, the prepared solid electrolyte has excellent ionic conductivity, chemical and electrochemical stability, excellent mechanical strength, and can reduce the preparation cost. At the same time, the preparation method of the solid electrolyte is simple and easy to mass produce. DETAILED DESCRIPTION
[0012] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0013] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0014] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0015] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0016] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0017] In this document, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features.
[0018] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0019] 1. Solid electrolyte
[0020] One or more embodiments of the present application provide a solid electrolyte, including an inorganic ceramic filler, a polymer and a lithium salt; the inorganic ceramic filler includes a first filler and a second filler; based on the total mass of the solid electrolyte, the mass content of the first filler is A%, and the mass content of the second filler is B%; wherein, 5≤A≤50; 0≤B≤25; 5≤A+B≤50; 0%≤B / A≤100%.
[0021] In some embodiments, based on the total mass of the solid electrolyte, the mass content of the first filler is 5, 8, 10, 13, 15, 18, 20, 23, 25, 28, 30, 33, 35, 38, 40, 43, 45, 48, 50 or a range consisting of any two of the above values. In some embodiments, the mass content of the second filler is 0, 3, 5, 8, 10, 13, 15, 18, 20, 23, 25 or a range consisting of any two of the above values. In some embodiments, the value of A+B is 5, 8, 10, 13, 15, 18, 20, 23, 25, 28, 30, 33, 35, 38, 40, 43, 45, 48, 50 or a range consisting of any two of the above values. In some embodiments, the value of B / A is 0, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, or a range consisting of any two of the above values. In some embodiments of the present application, 5≤A≤40; 0≤B≤20; 5≤A+B≤45; 0%≤B / A≤80%.
[0022] In some embodiments of the present application, inorganic ceramic fillers and polymers are mixed to form a solid electrolyte having high ionic conductivity and good interface contact performance. Furthermore, by adjusting the type and amount of the first filler and the second filler, a low-cost solid electrolyte with excellent ionic conductivity, chemical and electrochemical stability, and excellent mechanical strength can be prepared.
[0023] In some embodiments, when the content of the first filler exceeds a certain value, the first filler particles in the polymer matrix are prone to agglomeration, thereby weakening the lithium conductivity of the solid electrolyte, resulting in a decrease in the ionic conductivity of the electrolyte itself and a decrease in the electrochemical performance of the secondary battery; when the content of the first filler continues to increase to 90% or above, the density of the solid electrolyte is very large. It can be considered that the polymer acts as a binder between particles at this time, and the lithium conductivity of the solid electrolyte is positively correlated with its density. Therefore, the ionic conductivity will be improved. Although this can improve some electrochemical properties, the improvement is weak and this will lead to an increase in production costs, which is not conducive to industrial applications. Therefore, the content of the first filler is not the more the better.
[0024] In some embodiments of the present application, the price of the second filler may be different from the price of the first filler. Further, the price of the second filler may be lower than the price of the first filler. By using a suitable ratio of the first filler and the second filler, the production cost can be reduced without affecting the electrochemical properties of the final solid electrolyte, which is conducive to mass production in industrial applications.
[0025] In some embodiments, when the sum of the contents of the first filler and the second filler exceeds a certain value, no matter how the proportion of the two is distributed, the electrochemical performance of the solid electrolyte will be very poor, because no matter whether it is the first filler or the second filler, as long as the overall filler content is too high, the two particles will easily agglomerate, thereby weakening the lithium conductivity of the solid electrolyte; in some embodiments, when the sum of the contents of the first filler and the second filler is within a suitable range, and when the ratio of the content of the second filler to the content of the first filler is too large, the electrochemical performance of the solid electrolyte will decrease, because the chemical stability or electrochemical stability of the second filler is relatively poor. When the amount of the second filler introduced is too much, its own instability will be further amplified, thereby deteriorating the electrochemical performance of the solid electrolyte. The above situation shows that when a lower-cost second filler is used to partially replace a higher-cost first filler, there is a reasonable range that can be dynamically changed. It also shows that when this solution is applied to industrial production, it is possible to select an economical and excellent performance solution by balancing the electrochemical performance of the solid electrolyte and the cost of the inorganic ceramic filler.
[0026] In some embodiments of the present application, the first filler is but not limited to Li 3+X1 W X1 Zr 2-X1 Si2PO 12 , wherein 0≤X1≤2, W is at least one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y and Sn; the second filler includes but is not limited to Li 1+X2 M X2 (N1y1,N2y2,N3y3)2-X2 (PO4)3、Li 7-X3 Ln3Z 2-X3 Ta X3 O 12 and Li 7+X4 Zn X4 La 3-X4 Zr2O 12 At least one of, wherein 0.1≤X2≤0.9, y1+y2+y3=1, 0≤y1 / y2 / y3≤1, M is at least one of Al, Ga, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb, N1, N2, N3 are at least one of Ti, Ge and Hf, 0≤X3≤3, 0≤X4≤3;
[0027] In some embodiments of the present application, the first filler is but not limited to Li3Zr2Si2PO 12 (LZSP); the second filler includes but is not limited to Li 1.3 Al 0.3 Ti 1.7 P3O 12 (LATP), Li 1.5 Al 0.5 Ge 1.5 P3O 12 (LAGP), Li 1.5 Al 0.5 Hf 1.5 P3O 12 (LAHP), Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLZTO) and Li7La3Zr2O 12 At least one of (LLZO).
[0028] In some embodiments of the present application, based on the total mass of the solid electrolyte, the content of the inorganic ceramic filler is 5% to 50%. In some embodiments, based on the total mass of the solid electrolyte, the content of the inorganic ceramic filler is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the solid electrolyte, the content of the inorganic ceramic filler is 5% to 45%. In some embodiments, based on the total mass of the solid electrolyte, the content of the inorganic ceramic filler is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or a range consisting of any two of the above values.
[0029] If the relative content of inorganic ceramic filler is too low, the intrinsic ionic conductivity of the solid electrolyte is low, and its corresponding ion transmission capacity is too weak. At the same time, the mechanical strength of the solid electrolyte with low content of inorganic ceramic filler is limited, and it is not enough to effectively inhibit the growth of lithium dendrites, thereby affecting the cycle performance and safety of the battery. If the content of inorganic ceramic filler is too high, it is easy to form agglomeration between particles, resulting in uneven distribution of inorganic ceramic filler in the polymer matrix, thereby deteriorating the ion transmission capacity of the solid electrolyte. At the same time, the uneven distribution of inorganic ceramic filler is also easy to cause uneven lithium deposition, thereby deteriorating the safety of the battery. Therefore, controlling the content of inorganic ceramic filler within the above range is conducive to the inorganic ceramic filler to give full play to its own high mechanical strength and high stability characteristics, which is conducive to improving interface stability and improving battery safety; the introduction of an appropriate amount of inorganic ceramic filler can also effectively improve ionic conductivity, improve the ion conduction capacity of the solid electrolyte, and thus improve the cycle performance of the battery.
[0030] In some embodiments of the present application, the mass ratio of the polymer, the lithium salt, the first filler and the second filler is (20-60): (10-50): (5-50): (0-25). In some embodiments of the present application, the mass ratio of the polymer, the lithium salt, the first filler and the second filler is (30-50): (20-40): (10-40): (0-20).
[0031] In some embodiments of the present application, the polymer includes at least one of polyethylene oxide, polyethylene carbonate, polyetherimide, polyvinyl alcohol, polyvinylidene fluoride, polyethylene glycol, polymethyl methacrylate and polyacrylonitrile; in some embodiments, the polymer includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN).
[0032] In some embodiments of the present application, based on the total mass of the solid electrolyte, the content of the polymer is 20% to 60%.
[0033] In some embodiments of the present application, the lithium salt includes at least one of lithium bis(trifluoromethylimide), lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorophosphate. In some embodiments, the lithium salt includes lithium bis(fluorosulfonyl)imide (LiFSI).
[0034] In some embodiments of the present application, based on the total mass of the solid electrolyte, the content of the lithium salt is 10% to 50%.
[0035] In some embodiments, the shape and size of the solid electrolyte mainly depends on the container used when drying the mixed solution. The material of the container is not limited as long as it does not affect the performance of the final solid electrolyte. The shape of the solid electrolyte includes but is not limited to rectangular, circular, square, and irregular. The thickness of the solid electrolyte depends on the amount of mixed solution used in the preparation process and the size of the container.
[0036] In some embodiments, the thickness of the solid electrolyte is 100 μm to 150 μm. Exemplarily, the thickness of the solid electrolyte is 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, or a range consisting of any two of the above values. It is understandable that if the thickness of the solid electrolyte is too large, it will extend the transmission path of lithium ions between the positive and negative electrodes, affect the transmission efficiency of lithium ions, and affect the cycle performance and power performance of the battery. If the thickness of the solid electrolyte is too small, it will increase the manufacturing cost and production difficulty, which is not conducive to industrial application.
[0037] 2. Preparation method of solid electrolyte
[0038] One or more embodiments of the present application further provide a method for preparing a solid electrolyte, which is used to prepare the solid electrolyte of the aforementioned embodiment, and the preparation method comprises:
[0039] Step 1, mixing a polymer, a lithium salt, a first filler, and a second filler with a solvent in a mass ratio of (20-60): (10-50): (5-50): (0-25) to prepare a mixed solution;
[0040] Step 2, removing excess solvent from the mixed solution obtained in step 1 to obtain a solid electrolyte;
[0041] In some embodiments, the solid electrolyte can be prepared only by mixing and then drying, without the need for additional complex equipment or cumbersome processes. The manufacturing process is simple, cost-controllable, and conducive to large-scale production in business. The solid electrolyte prepared by the preparation method of the present application is thin and the inorganic ceramic filler is evenly distributed. In addition, the thinner solid electrolyte with excellent ionic conductivity can also shorten the conduction distance of lithium ions. Furthermore, the solid electrolyte can also optimize the interface performance between it and the electrode in the secondary battery; thus, the cycle performance of the secondary battery can be improved.
[0042] In some embodiments, in step 1, preparing the mixed solution comprises the following steps:
[0043] Step 1-1, dissolving the polymer in an organic solvent in an inert atmosphere, stirring at room temperature to clarify, then adding lithium salt, and stirring at room temperature until completely dissolved;
[0044] Step 1-2, adding an inorganic ceramic filler to the solution obtained in step 1-1, and obtaining a mixed solution after ultrasonic treatment and stirring.
[0045] In some embodiments, step 1-2 comprises ultrasonicating the solution after adding the inorganic ceramic filler at 40° C. to 60° C. for 1 h to 2 h in an inert atmosphere, and then stirring at room temperature for 12 h to 24 h to obtain a mixed solution.
[0046] In some embodiments, step 2 comprises placing the mixed solution obtained in step 1 in a container and drying it in an inert atmosphere to obtain the solid electrolyte.
[0047] In some embodiments, the inert atmosphere includes, but is not limited to, an argon atmosphere.
[0048] In some embodiments, the drying temperature in an inert atmosphere is 60°C to 90°C. Exemplarily, the drying temperature in an inert atmosphere is 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or a range consisting of any two of the above values.
[0049] It is understandable that if the drying temperature is too low, the solvent evaporates slowly, making the preparation time too long; while if the drying temperature is too high, the solvent evaporates quickly, causing the viscosity of the liquid film formed after the mixed solution is coated to increase too quickly, so that the formed modified layer has more pinholes or even forms a morphology similar to "orange peel", thereby deteriorating the performance of the secondary battery. Controlling the drying temperature within the above range can take into account both the preparation time and film formation, which is conducive to the realization of practical applications in business.
[0050] In some embodiments, the drying time is 12 h to 24 h. Exemplarily, the drying time is 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h or a range consisting of any two of the above values.
[0051] It is understandable that the drying time is negatively correlated with the drying temperature. The higher the drying temperature, the shorter the drying time, and the lower the drying temperature, the longer the drying time.
[0052] In some embodiments, the amount of each mixed solution is 15ml to 40ml. Exemplarily, the amount of each mixed solution is 15ml, 16ml, 18ml, 20ml, 22ml, 24ml, 26ml, 28ml, 30ml, 32ml, 34ml, 36ml, 38ml, 40ml, or a range consisting of any two of the above values. In some embodiments, the amount of each mixed solution is 20ml to 25ml. Exemplarily, the amount of each mixed solution is 20ml.
[0053] In some embodiments, the polymer includes, but is not limited to, at least one of polyethylene oxide, polyethylene carbonate, polyetherimide, polyvinyl alcohol, polyvinylidene fluoride, polyethylene glycol, polymethyl methacrylate, and polyacrylonitrile.
[0054] In some embodiments, the viscosity of the mixed solution is 500cP to 3000cP; illustratively, the viscosity of the mixed solution is 500cP, 600cP, 800cP, 1000cP, 1200cP, 1400cP, 1500cP, 1600cP, 1800cP, 2000cP, 2200cP, 2400cP, 2500cP, 2600cP, 2800cP, 3000cP or a range consisting of any two of the above values. If the viscosity of the mixed solution is too large, the uniformity of the modified layer formed is poor and the performance of the modified layer is poor; if the viscosity is too small, the spin coating process is difficult to implement, so that the formed modified layer will be too thin and it is difficult to achieve an effective interface improvement effect.
[0055] In some embodiments, based on the mass of the mixed solution, the mass fraction of the polymer is 5wt% to 20wt%; illustratively, based on the mass of the mixed solution, the mass fraction of the polymer is 5wt%, 6wt%, 8wt%, 10wt%, 13wt%, 15wt%, 18wt%, 20wt% or a range consisting of any two of the above values. The polymer concentration is positively correlated with the viscosity of the mixed solution. Too high a polymer concentration will cause the viscosity of the mixed solution to be too large and difficult to spread, resulting in poor uniformity of the solid electrolyte formed, which will deteriorate the interface performance between the electrode and the solid electrolyte; too low a polymer concentration corresponds to excessive solvent content in the mixed solution, thereby extending the drying time of the mixed solution and affecting the preparation efficiency of the solid electrolyte.
[0056] In some embodiments, the inorganic ceramic filler includes a first filler and a second filler;
[0057] In some embodiments, the first filler includes Li 3+X1 W X1 Zr 2-X1 Si2PO 12 , wherein 0≤X1≤2, W is at least one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y and Sn; the second filler includes Li 1+X2 M X2 (N 1Y1 ,N 2Y2 ,N 3Y3 ) 2-X2 (PO4)3、Li 7-X3 Ln3Z 2-X3 Ta X3 O12 and Li 7+X4 Zn X4 La 3-X4 Zr2O 12 At least one of the following, wherein 0.1≤X2≤0.9, Y1+Y2+Y3=1, 0≤Y1 / Y2 / Y3≤1, M is at least one of Al, Ga, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb, N1, N2, N3 are at least one of Ti, Ge and Hf respectively, 0≤X3≤3, 0≤X4≤3.
[0058] In some embodiments, the first filler comprises Li3Zr2Si2PO 12 (LZSP); the second filler includes Li 1.3 Al 0.3 Ti 1.7 P3O 12 (LATP), Li 1.5 Al 0.5 Ge 1.5 P3O 12 (LAGP), Li 1.5 Al 0.5 Hf 1.5 P3O 12 (LAHP), Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLZTO) and Li7La3Zr2O 12 At least one of (LLZO).
[0059] Based on the total mass of the solid electrolyte, the mass content of the first filler is A%, and the mass content of the second filler is B%; wherein, 5≤A≤50; 0≤B≤25; 5≤A+B≤50; 0%≤B / A≤100%.
[0060] In some embodiments, 5≤A≤40; 0≤B≤20; 5≤A+B≤45; 0%≤B / A≤80%.
[0061] In some embodiments, based on the total mass of the polymer and the inorganic ceramic filler, the mass fraction of the inorganic ceramic filler is 5wt% to 60wt%. Exemplarily, based on the total mass of the polymer and the inorganic ceramic filler, the mass fraction of the inorganic ceramic filler is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt% or a range consisting of any two of the above values. In some embodiments, based on the total mass of the polymer and the inorganic ceramic filler, the mass fraction of the inorganic ceramic filler is 5wt% to 50wt%.
[0062] In some embodiments, the lithium salt includes, but is not limited to, at least one of lithium bis(trifluoromethylimide), lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorophosphate.
[0063] In some embodiments, the concentration of the lithium salt in the mixed solution is 0.5 mol / L to 2.5 mol / L. Exemplarily, the concentration of the lithium salt in the mixed solution is 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L, 2.5 mol / L or a range consisting of any two of the above values.
[0064] It is understandable that if the lithium salt concentration is too low, the ionic conductivity of the solid electrolyte will decrease, and it may also lead to uneven distribution of lithium ions and unstable electrochemical interface; if the lithium salt concentration is too high, the viscosity of the mixed solution will increase, thus affecting the preparation of the solid electrolyte. At the same time, too much lithium salt cannot be utilized by the polymer chain segments, which will also reduce the ionic conductivity of the solid electrolyte. Controlling the lithium salt concentration within the above range can ensure the rapid conduction of lithium ions in the solid electrolyte, which in turn helps to improve the overall performance of the full secondary battery.
[0065] In some embodiments, the solvent comprises at least one of tetrahydrofuran, acetonitrile, and N,N-dimethylformamide. In some embodiments, the solvent comprises N,N-dimethylformamide.
[0066] In some embodiments, based on the mass of the mixed solution, the mass fraction of the solvent is 60 wt % to 90 wt %.
[0067] 3. Secondary battery
[0068] One or more embodiments of the present application also provide a secondary battery, comprising the solid electrolyte of the aforementioned embodiment or the solid electrolyte prepared by the aforementioned method for preparing the solid electrolyte. In some embodiments, the secondary battery comprises a positive electrode sheet, a solid electrolyte, and a negative electrode sheet.
[0069] The materials, compositions and manufacturing methods of the positive electrode sheets that can be used in the embodiments of the present application include any technology disclosed in the prior art.
[0070] In some embodiments, the positive electrode sheet of the present application includes: a positive electrode current collector and a positive electrode active material layer located on the surface of the positive electrode current collector, wherein the positive electrode active material of the positive electrode active material layer includes: at least one of a nickel-cobalt ternary material and a phosphate-based material; the nickel-cobalt ternary material includes LiNi x Co y M (1-x-y) At least one of the O2 materials, M includes at least one of Mn, Al, Mg, Cr, Ca, Zr, Mo, Ag, Nb, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; the phosphate material includes LiMn k B (1-k) PO4, wherein 0≤k≤1, and the B element comprises at least one of iron, cobalt, magnesium, calcium, zinc, chromium or lead.
[0071] In some embodiments, the positive electrode sheet active material layer further includes a conductive agent and a binder. The positive electrode active material, conductive agent, and binder are fully stirred and mixed in a solvent system in a certain proportion, applied on the positive electrode current collector, dried, and rolled to obtain a positive electrode sheet.
[0072] In some embodiments, the conductive agent includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0073] In some embodiments, the binder includes but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.
[0074] The materials, compositions and manufacturing methods of the negative electrode sheets that can be used in the embodiments of the present application include any technology disclosed in the prior art.
[0075] In some embodiments, the negative electrode plate involved in the present disclosure includes a negative electrode current collector and a negative electrode material layer, the negative electrode material layer is arranged on the surface of the negative electrode current collector, and the negative electrode material layer includes a negative electrode active material. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments of the present application, the negative electrode active material includes at least one of silicon-based materials, carbon-based materials, tin-based materials, phosphorus-based materials, lithium metal or lithium alloys. The silicon-based material includes at least one of silicon, silicon alloys, silicon oxide compounds and silicon carbon compounds. The carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene. The tin-based material includes at least one of tin, tin oxide and tin alloy. The phosphorus-based material includes phosphorus and / or phosphorus complexes.
[0076] In some embodiments, the negative electrode material layer further comprises a binder, and based on the total mass of the negative electrode material layer, the mass percentage of the binder is 0.3%-5%. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0077] In some embodiments, non-limiting examples of the binder include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0078] In some embodiments, the negative electrode material layer may further include a conductive agent, and the mass percentage of the conductive agent is 0.3%-3% based on the total mass of the negative electrode material layer. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0079] In some embodiments, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0080] In some embodiments, the negative electrode plate is lithium metal or lithium alloy.
[0081] In some embodiments, the lithium alloy includes lithium and a metal / metalloid that can be alloyed with lithium. For example, the metal / metalloid that can be alloyed with lithium is Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y alloy (wherein Y is an alkali metal, an alkaline earth metal, an element of Group 13-16, a transition metal, a rare earth element, or a combination thereof, except Si), or Sn-Y alloy (wherein Y is an alkali metal, an alkaline earth metal, an element of Group 13-16, a transition metal, a rare earth element, or a combination thereof, except Sn). Y can be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po or a combination thereof.
[0082] In some embodiments, the negative electrode is lithium metal.
[0083] 4. Device
[0084] One or more embodiments of the present application further provide a device including the secondary battery of the aforementioned embodiment.
[0085] In some embodiments, the devices of the present application include but are not limited to: laptop computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.
[0086] The technical solution of the present application will be further described below in conjunction with specific examples and comparative examples. The following examples and comparative examples are only used to exemplify the inventive concept of the present application and are not used to limit the present application.
[0087] Examples and Comparative Examples
[0088] Example 1
[0089] Preparation of positive electrode
[0090] The positive electrode sheet NCM523 (active material is LiNi 0.5 Co 0.2 Mn 0.3O2), conductive agent carbon nanotube / acetylene black (CNT / Super-P), binder polyvinylidene fluoride (PVDF), by weight proportion LiNi 0.5 Co 0.2 Mn 0.3 O2:CNT / Super-P:PVDF=95:2.0 / 1.0:2 was fully slurried in N-methylpyrrolidone (NMP) solvent system, coated on a 12 μm thick aluminum current collector, dried, and roll-pressed to obtain a positive electrode sheet.
[0091] Preparation of negative electrode
[0092] A lithium metal sheet with a diameter of 12 mm and a thickness of 0.3 mm was cut as the negative electrode sheet.
[0093] Preparation of solid electrolyte
[0094] Step 1, 0.3 g PVDF was dissolved in 5 g DMF in an argon atmosphere, and then stirred at room temperature for 4 h until the solution was clear, and then 0.16 g LiFSI was added, and then stirred at room temperature for 4 h until the lithium salt was fully dissolved.
[0095] Step 2, adding 0.051 g of the first filler and 0 g of the second filler to the mixed solution obtained in step 1 to obtain a mixed solution, placing the mixed solution at 45° C. for 1 h to allow the powder to be fully dispersed, and then stirring at room temperature for 16 h to obtain a uniformly dispersed mixed solution containing an inorganic ceramic filler;
[0096] Step 3, take 20 ml of the uniformly dispersed mixed solution obtained in step 2 and pour it on a glass vessel with a diameter of 10 cm, and dry it at 70° C. in an inert atmosphere for 12 h to fully evaporate the solvent to obtain a solid electrolyte membrane with a thickness of about 120 μm and containing 10% LZSP.
[0097] Assembly of secondary batteries
[0098] The prepared NCM523 positive electrode sheet, the dried solid electrolyte, and the lithium metal negative electrode sheet are sequentially placed in the CR2032 positive electrode sheet shell, and the positive and negative electrode sheets are adjusted. After the electrolyte is in the center of the positive electrode sheet shell, the CR2032 negative electrode sheet shell is covered. The assembled button battery is placed in the button battery sealing machine mold, and the pressure is set to 800Pa for pressing to obtain the secondary battery in the embodiment.
[0099] Example 2-11
[0100] The difference between Example 2-11 and Example 1 is that the mass content of the first filler and the second filler is changed, see Table 1 for details.
[0101] The rest of the preparation method is the same as that in Example 1.
[0102] Examples 12-14
[0103] The only difference between Examples 12-14 and Example 4 is that the type of polymer is changed, see Table 1 for details.
[0104] The rest of the preparation method is the same as that in Example 4.
[0105] Examples 15-16
[0106] The difference between Examples 15-16 and Example 4 is that when forming the solid electrolyte, the temperature of the drying process in the inert atmosphere is different, see Table 1 for details.
[0107] The rest of the preparation method is the same as that in Example 4.
[0108] Comparative Example 1
[0109] The only difference between Comparative Example 1 and Example 4 is that the first filler and the second filler are not added.
[0110] The rest of the preparation method is the same as that in Example 4.
[0111] Comparative Examples 2-3
[0112] The difference between Comparative Example 2-3 and Example 1 is that the second filler is not added and the mass content of the first filler is too much, see Table 1 for details.
[0113] The rest of the preparation method is the same as that in Example 1.
[0114] Comparative Examples 4-5
[0115] The only difference between Comparative Example 4-5 and Example 4 is that the mass contents of the first filler and the second filler are different and both are within the normal range, but the mass ratio of the second filler to the first filler is too large.
[0116] The rest of the preparation method is the same as that in Example 4.
[0117] Comparative Example 6
[0118] The only difference between Comparative Example 6 and Example 4 is that the mass contents of the first filler and the second filler are different and both are within the normal range, but the sum of the mass contents of the second filler and the first filler is excessive.
[0119] The rest of the preparation method is the same as that in Example 4.
[0120] Comparative Examples 7-8
[0121] The only difference between Comparative Examples 7-8 and Example 4 is that the first filler is not added and the mass content of the first filler is within the normal range.
[0122] The rest of the preparation method is the same as that in Example 4.
[0123] Comparative Example 9
[0124] The only difference between Comparative Example 9 and Example 4 is that the mass contents of the first filler and the second filler are different, the mass content of the first filler is within a normal range, but the mass content of the second filler is excessive.
[0125] The rest of the preparation method is the same as Example 4.
[0126] Test Method
[0127] 1. Ionic conductivity of solid electrolyte at room temperature (25°C)
[0128] The solid electrolyte prepared in the embodiment and comparative example was assembled with a stainless steel electrode into a stainless steel / solid electrolyte / stainless steel battery to test the ionic conductivity at room temperature 25°C. The ionic conductivity calculation formula is: σ=d / RS (0.1Hz~1MHz; 5mV), where d is the thickness of the solid electrolyte membrane, R is the impedance obtained by the test, and S is the area of the solid electrolyte. The calculation results are recorded in Table 1.
[0129] 2. Capacity retention rate after 100 cycles at 25°C
[0130] The solid electrolytes prepared in the embodiments and comparative examples were assembled into button-type full batteries with lithium metal pole pieces and NCM523 positive pole pieces. The voltage range was set to 2.5V-4.3V and the current density parameters were set to 0.1C. The cycle capacity of the full batteries corresponding to the solid electrolytes obtained in different embodiments and comparative examples was recorded, and the capacity retention rate after 100 cycles was compared and recorded in Table 1.
[0131] 3. Solid electrolyte thickness
[0132] The thickness of the solid electrolyte prepared in the embodiment and the comparative example is recorded by a spiral thickness gauge as D;
[0133] As shown in Table 1, it can be seen from the data of Comparative Example 1 that the solid electrolyte without inorganic ceramic filler, that is, only containing polymer and lithium salt, has very low ion conductivity and weak ion transmission capacity. In addition, the lack of mechanical strength and stability brought by inorganic ceramic filler also easily generates lithium dendrites, thereby deteriorating the cycle performance and safety of the battery.
[0134] It can be seen from the data of Examples 1-3 and Comparative Examples 2-3 that the more the first filler is added, the better. When an excessive amount of the first filler is used, the performance will be reduced. Compared with Comparative Example 2, the performance of Comparative Example 3 is slightly improved because the density of the inorganic ceramic filler is very high at this time, which is conducive to ion conduction.
[0135] It can be seen from the data of Examples 1-16 that by appropriately adjusting the type and content of the first filler and the second filler, the type of polymer, and the ultrasonic temperature / duration and drying temperature / duration during the preparation process, a solid electrolyte with excellent electrochemical properties can be obtained.
[0136] It can be seen from Comparative Examples 4 and 5 that when the proportion of the second filler relative to the first filler is too high, it is not conducive to the room temperature ionic conductivity of the solid electrolyte and the room temperature cycle performance of the secondary battery.
[0137] It can be seen from Comparative Examples 2 and 6 that regardless of the unilateral excess of the first filler or the content and excess of the first filler and the second filler, the room temperature ionic conductivity of the solid electrolyte in both cases is low and the room temperature cycle performance of the secondary battery is very poor.
[0138] It can be seen from Comparative Examples 7 and 8 that when only the second filler is added to the solid electrolyte, the room temperature cycle performance of the secondary battery can also be improved, but the effect is limited; when the first filler and the second filler are used in the solid electrolyte at the same time, the improvement in the performance of the secondary battery is particularly significant and the cost is controllable.
[0139] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
[0140]
[0141]
Claims
1. A solid electrolyte, characterized in that It includes a polymer, a lithium salt and an inorganic ceramic filler; the inorganic ceramic filler includes a first filler and a second filler; based on the total mass of the solid electrolyte, the mass content of the first filler is A%, and the mass content of the second filler is B%; wherein, 5≤A≤50; 0≤B≤25; 5≤A+B≤50; 0%≤B / A≤100%.
2. The solid electrolyte according to claim 1, characterized in that 5≤A≤40; 0≤B≤20; 5≤A+B≤45; 0%≤B / A≤80%.
3. The solid electrolyte according to claim 1, characterized in that The first filler includes Li 3+X1 W X1 Zr 2- X1 Si2PO 12 , wherein 0≤X1≤2, W is at least one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y and Sn; The second filler includes Li 1+X2 M X2 (N 1Y1 ,N 2Y2 ,N 3Y3 ) 2-X2 (PO4)3、Li 7-X3 LqCy 2-X3 Ta X3 O 12 and Li 7+ X4 Zn X4 La 3-X4 Zr2O 12 At least one of the following, wherein 0.1≤X2≤0.9, Y1+Y2+Y3=1, 0≤Y1 / Y2 / Y3≤1, M is at least one of Al, Ga, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb, N1, N2, N3 are at least one of Ti, Ge and Hf respectively, 0≤X3≤3, 0≤X4≤3.
4. The solid electrolyte according to claim 3, characterized in that The first filler includes Li3Zr2Si2PO 12 ; The second filler includes Li 1.3 Al 0.3 Ti 1.7 P3O 12 , Li 1.5 Al 0.5 Ge 1.5 P3O 12 , Li 1.5 Al 0.5 Hf 1.5 P3O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 and Li7La3Zr2O 12 At least one of .
5. The solid electrolyte according to claim 1, characterized in that At least one of the following conditions is also met: (a) the polymer comprises at least one of polyethylene oxide, polyethylene carbonate, polyetherimide, polyvinyl alcohol, polyvinylidene fluoride, polyethylene glycol, polymethyl methacrylate and polyacrylonitrile; (b) the lithium salt comprises at least one of lithium bis(trifluoromethylimide), lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate and lithium difluorophosphate; (c) The mass ratio of the polymer, the lithium salt, the first filler and the second filler is (20-60): (10-50): (5-50): (0-25); (d) The solid electrolyte has a thickness of 100 μm to 150 μm.
6. A method for preparing a solid electrolyte as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises: Step 1, mixing a polymer, a lithium salt, a first filler, and a second filler with a solvent in a mass ratio of (20-60): (10-50): (5-50): (0-25) to prepare a mixed solution; Step 2, removing the solvent in the mixed solution obtained in step 1 to obtain a solid electrolyte.
7. The method for preparing a secondary battery according to claim 6, characterized in that: The solvent comprises at least one of tetrahydrofuran, acetonitrile and N,N-dimethylformamide; and / or Step 1 comprises mixing a polymer, a lithium salt, a first filler, a second filler and a solvent in a mass ratio of (20-60): (10-50): (5-50): (0-25) in an inert atmosphere, ultrasonicating at 40° C. to 60° C. for 1 h to 2 h, and then stirring at room temperature for 12 h to 24 h to obtain the mixed solution; and / or Step 2 comprises drying the mixed solution obtained in step 1 at 60° C. to 90° C. for 12 h to 24 h in an inert atmosphere to obtain the solid electrolyte.
8. The preparation method according to claim 7, characterized in that: The viscosity of the mixed solution is 500 cP to 3000 cP; and / or The mass content of the polymer is 5 wt % to 20 wt % based on the total mass of the mixed solution.
9. A secondary battery, characterized in that: The invention comprises the solid electrolyte according to any one of claims 1 to 5 or the solid electrolyte prepared by the preparation method according to any one of claims 6 to 8.
10. A device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.